2021
DOI: 10.1371/journal.pone.0251056
|View full text |Cite
|
Sign up to set email alerts
|

Association between number of teeth and Alzheimer’s disease using the National Database of Health Insurance Claims and Specific Health Checkups of Japan

Abstract: Associations of numbers of teeth present and of missing teeth with Alzheimer’s disease were cross-sectionally analyzed using the National Database of Health Insurance Claims and Specific Health Checkups of Japan. Dental care claims data of patients aged 60 years or older diagnosed with periodontitis (n = 4,009,345) or missing teeth (n = 662,182) were used to obtain information about the numbers of teeth present and of missing teeth, respectively, and they were combined with medical care claims data including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Participants in this study also had more teeth than other reports of older people with dementia in Japan [40]. Older people with more remaining teeth, subjective chewing and no oral pain are therefore less likely to see a dentist [41]. Periodontal disease is generally painless, and thus people with dementia who have periodontal disease tend not to go to the dentist, and may therefore have unmet oral care needs.…”
Section: Discussionmentioning
confidence: 66%
“…Participants in this study also had more teeth than other reports of older people with dementia in Japan [40]. Older people with more remaining teeth, subjective chewing and no oral pain are therefore less likely to see a dentist [41]. Periodontal disease is generally painless, and thus people with dementia who have periodontal disease tend not to go to the dentist, and may therefore have unmet oral care needs.…”
Section: Discussionmentioning
confidence: 66%
“…There was no association between number of present teeth and dementia in our study. Past studies were reported that missing tooth is associated with development of Alzheimer's dementia 36 . This may be related to number of participants with missing tooth.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Another recent study of national database from Japan reported that older people with fewer teeth were more likely to develop Alzheimer’s disease. 23 …”
Section: Discussionmentioning
confidence: 99%